2015
DOI: 10.20429/ijsotl.2015.090211
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Graduate Student Instructors in Calculus

Abstract: This paper focuses on the use of the teaching method Peer-Assisted Reflection (PAR) to help graduate student instructors (GSIs) develop as teachers. PAR engages students in analyzing the work of their peers and providing feedback to promote their abilities of communication, collaboration, and persistence. The goals of the PAR activity were taken as goals for instruction generally, and used to support the GSIs to develop student-centered pedagogies. This report provides in depth case studies of two of four GSIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…By contrast, a growing body of evidence suggests that when GTAs have been involved in peer (specifically equal-status) observation or peer review of teaching projects, there are significant benefits to the development of their self-critique and reflective thinking skills (Reinholz, Cox and Croke, 2015;Howlett and Nguyen, 2020). Reinholz's (2017) study of Mathematics GTAs also found that observing and giving feedback to each other encouraged them to feel less isolated in their roles and part of a professional learning community sharing similar worries, concerns and challenges.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, a growing body of evidence suggests that when GTAs have been involved in peer (specifically equal-status) observation or peer review of teaching projects, there are significant benefits to the development of their self-critique and reflective thinking skills (Reinholz, Cox and Croke, 2015;Howlett and Nguyen, 2020). Reinholz's (2017) study of Mathematics GTAs also found that observing and giving feedback to each other encouraged them to feel less isolated in their roles and part of a professional learning community sharing similar worries, concerns and challenges.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…There is recognition of the value of observation experiences for GTA development and recent years have seen a growing focus on them as an area for research and investigation. For example, Reinholz, Cox and Croke (2015) and Reinholz (2017) report findings from projects involving Mathematics GTAs in a peer observation or peer review process. Sozer, Zeybekoglu and Alayli (2019) discuss the benefits emerging for GTAs from observed micro-teaching activities.…”
Section: Introductionmentioning
confidence: 99%
“…Although changes in instructor teaching practices were not analyzed, prior research showed that working with instructors in the same department in a similar setting resulted in measurable changes in practices (Reinholz, Cox, & Croke, 2015).…”
Section: Objective Observersmentioning
confidence: 99%